Multilayer silica-methacrylate hybrid coatings prepared by sol-gel on stainless steel 316L: Electrochemical evaluation - López, Damián A. (2008)
AISI 316L stainless steel is a biocompatible alloy used in prosthetic devices for many years. However this alloy tends to suffer localized corrosion and needs external fixation to hard tissues. This work describes the development of a coating system of two layers with complementary properties. The inner layer is prepared using TEOS and MTES that has already shown good anticorrosion properties. The top layer is a new hybrid organic-inorganic coating prepared with TEOS, 3-methacryloxypropyl trimethoxysilane (MPS), and 2-hydroxyethyl methacrylate (HEMA). The properties of this sol let to produce a thick and porous coating formed by two interpenetrating (organic and inorganic) networks. This coating could be an excellent container for the later aggregate of bioactive particles as the following step in a future work based on its high thickness, plasticity and open structure to allow the electrolyte access to induce the formation of hydroxyapatite. The coating is electrochemically characterised in simulated body fluid at 37 °C after 1, 10 and 30 days of immersion by means of assays as electrochemical impedance spectroscopy (EIS) and polarization curves. The dual coating seems to join the best properties of the individual ones in time: their thickness restrict the passage of potentially toxic ions to the body fluid, the breakdown potential (Eb) remains high and far from the corrosion potential (Ecorr) and the film presents the open structure of the outer layer that allows the entrance of the electrolyte to react with the particles when added to the sol meanwhile the inner layer maintain its corrosion protective features.